Analysis of biomarkers in a Czech population exposed to heavy air pollution. Part II: chromosomal aberrations and oxidative stress - Rossner, Pavel; Rossnerova, Andrea; Spatova, Milada; Beskid, Olena; Uhlirova, Katerina; Libalova, Helena; Solansky, Ivo; Topinka, Jan; Sram, Radim J (Mutagenesis, 2013)
Populations living in industrialised regions are at higher risk of a number of diseases and shortened life span. These negative effects are primarily brought about by damage to cells and macromolecules caused by environmental pollutants. In this study, we analysed the effect of exposure to benzo[a]pyrene, a particulate matter of aerodynamic diameter < 2.5 µm (PM2.5), and benzene on oxidative stress markers [including 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), 15-F(2t)-isoprostane (15-F2t-IsoP) and protein carbonyls] and cytogenetic parameters (stable and unstable chromosomal aberrations). The samples were collected from subjects living in the Ostrava region characterised by very high levels of air pollution and in Prague with comparatively lower concentrations of pollutants in three seasons (winter 2009, summer 2009 and winter 2010). Despite several-fold higher concentrations of air pollutants in the Ostrava region, the levels of stable aberrations (genomic frequency of translocations per 100 cells, percentage of aberrant cells and frequency of acentric fragments) were mostly comparable in both locations. The frequency of unstable aberrations measured as the number of micronuclei was unexpectedly significantly lower in the Ostrava region subjects in both seasons of 2009. Urinary excretion of 8-oxodG did not differ between locations in either season. Lipid peroxidation measured as levels of 15-F2t-IsoP in blood plasma was elevated in the Ostrava subjects sampled in 2009. Protein oxidation was higher in Prague samples collected in summer 2009. Multivariate analyses conducted separately in subjects from Prague and Ostrava showed a negative association between the frequency of micronuclei and concentrations of benzo[a]pyrene and PM2.5 in both regions. A positive relationship was observed between lipid peroxidation and air pollution; protein oxidation seems to be positively affected by PM2.5 in both regions.
Keywords: Oxidative Stress; Isoprostanes; oxidační stres; pevné částice; Humans; Lymphocytes; lidé středního věku; lymfocyty; Deoxyguanosine; isoprostany; Multivariate Analysis; dospělí; peroxidace lipidů; Protein Carbonylation; lidé; Air Pollution; Air Pollutants; Biomarkers; karbonylace proteinů; Particulate Matter; Dinoprost; látky znečišťující vzduch; Adult; Cities; 8-Hydroxy-2'-Deoxyguanosine; chromozomální aberace; biologické markery; multivariační analýza; Chromosome Aberrations; Male; Middle Aged; deoxyguanosin; Benzo(a)pyrene; Czech Republic; znečištění ovzduší; 8-hydroxy-2'-deoxyguanosin; Česká republika; mužské pohlaví; benzopyren; velkoměsta; dinoprost; Lipid Peroxidation